2022
DOI: 10.3389/fpsyg.2021.791850
|View full text |Cite
|
Sign up to set email alerts
|

Buying to Cope With Scarcity During Public Emergencies: A Serial Mediation Model Based on Cognition-Affect Theory

Abstract: Panic buying is a common phenomenon that occurs during public emergencies and has a significant undesirable impact on society. This research explored the effect of scarcity on panic buying and the role of perceived control and panic in this effect through big data, an online survey and behavior experiments in a real public emergency (i.e., COVID-19) and simulative public emergencies. The findings showed that scarcity aggravates panic buying (Studies 1–3), and this aggravation effect is serially mediated by per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…In emergency management studies, COVID-19 outbreak prevention and control approaches for travel [16], transport [17], and community [18] have achieved significant management performance. At the same time, research has been conducted on a range of social issues arising from the COVID-19 epidemic, such as the panic buying behavior of the public [19], the differential prevention strategies of people in different regions due to their cultural orientation [20], and the relationship between urban prosperity and the spread of the COVID-19 epidemic [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In emergency management studies, COVID-19 outbreak prevention and control approaches for travel [16], transport [17], and community [18] have achieved significant management performance. At the same time, research has been conducted on a range of social issues arising from the COVID-19 epidemic, such as the panic buying behavior of the public [19], the differential prevention strategies of people in different regions due to their cultural orientation [20], and the relationship between urban prosperity and the spread of the COVID-19 epidemic [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prosperity of big data has brought new vitality to different academic fields, such as mental health research ( Hassani et al, 2022 ; Liang et al, 2022 ), buying behavior research ( Ma and Liao, 2022 ; Wang J. et al, 2022 ), and so on. Among them, Internet search data is widely used with the advantage of easy access.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, people generate a cognition-affect-coping model when facing threats and pressure; that is, an individual’s cognition and judgment of risk stimuli produce a corresponding effect and then influence the individual’s response behavior [ 19 ]. A serial mediation model based on cognition-affect theory showed that scarcity aggravates panic buying, and this aggravation effect is serially mediated by perceived control and panic [ 20 ]. These findings provide essential enlightenment for guiding rational public behavior and managing public opinion during emergencies.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
“…However, the previous theories and models (TPB, cognition-affect theory) lack specificity in the context of COVID-19 crisis, and the specific public behavior theories were rarely reported. Furthermore, traditional statistical methods, such as principal component analysis, linear regression model, and path analysis [ 17 , 18 , 20 , 21 ], only clarify the quantitative correlation between the dependent and independent variables and cannot profoundly explain its further logical causality, which limits the theory’s explanatory power.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation